Expectations and realities a descriptive study on media and information literacy levels of Metro Manila senior high school millennials - Talusan, Irish Jane L. 1993-
The study describes the media literacy levels of senior high school learners through their exposure, knowledge, and usage of media by using the concepts of Potter's Cognitive Theory of Media literacy and Alagaran's Explore, Engage and Empower Model. A mixed-method research was implemented through conducting surveys among 197 respondents and focus group discussions among 17 participants from a subset sample of Grade 11 and 12 students of Rizal High School. Results and findings showed that senior high school millennials in the study are highly social media-based, and suggestive than reflective. They also prioritize being critical media users that being competent producers. The study concludes that to maximize the 80-hour Media and Information Literacy subject, curriculum developers should decide whether to promote or focus-promote traditional media, developmental orientation, and quality production of focus on learner-preferred social media, individual orientation, and critical thinking.